If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T + 28 = 51 Reorder the terms: 28 + T = 51 Solving 28 + T = 51 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + T = 51 + -28 Combine like terms: 28 + -28 = 0 0 + T = 51 + -28 T = 51 + -28 Combine like terms: 51 + -28 = 23 T = 23 Simplifying T = 23
| (x-2)(x+2)=32 | | .50/8x | | m-9=-13 | | W^2-11w+30.25=0 | | 9/6n-6 | | 64=4e | | 2x^2+20x+100=98 | | 5*24-3y+3y=36 | | 22+12.5= | | 16=3Y-2 | | 24u^8w^6+28u^2w^2x^9=0 | | -15x+19=7x+83 | | 84=-24t | | x*2+x=110 | | 3x+7x-2x-5=35 | | 4r^1/3 | | 8m=120 | | 4x-32y=-12 | | 1.1c+8.1=-2.9 | | 7200-1628x+83x^2+x^3=0 | | -2(4x-8)=112 | | inw=6+5x | | 7x=2w | | 4(t-8)20=5 | | 1/x4x | | -2(4x-8)=12 | | 2m+1=27 | | 6x+x-8=6x+7 | | 11k-11=7k-(-21) | | (8x^2+2x-6)-(5x^2-3x+2)=0 | | 2g-4=-8 | | 2(x-1)-3x=7 |